Introduction: Vibrant Materialities Across Media, Literature, and Theory - Tschofen, Monique; Fan, Lai-Tze (Imaginations: Journal of Cross-Cultural Image Studies, 2023)
This special issue of *Imaginations: Journal of Cross-Cultural Image Studies* takes materiality as the critical touchstone for a new comparative literary and media studies. We ask: How can an examination of the modes of inscription across media, platforms, and interfaces draw greater attention to what is often ignored in critical conversations about texts, objects, and bodies; how can such an investigation attend to the vitality of their materiality? Studies of materiality may occur of/in: images, texts, subjects, and objects; philosophical approaches to materiality and interrelationality; cultural considerations of user relationships to media materiality; mediums of scholarship, including critical applications in open-source publishing; critical making and research-creation; and experiences, interactions, and representations of digital spaces. Here, we take materiality to include actants, actors, inscriptions, assemblages, interfaces, objects, bodies, things and the things we think with, as well as their agencies and provocations. The papers reconsider the entanglements between inscription and representation and between inscription and world through theoretical frameworks that show that “matter matters,” using approaches that include code studies, critical making, digital humanities, ecocriticism, feminism, Marxism, media archaeology, new materialism, and phenomenology.